1993
DOI: 10.1113/jphysiol.1993.sp019594
|View full text |Cite
|
Sign up to set email alerts
|

Neural differentiation in cleavage‐arrested ascidian blastomeres induced by a proteolytic enzyme.

Abstract: SUMMARY1. As previously reported, ectodermal a4-2 blastomeres isolated from 8-cell embryos of the ascidian, Halocynthia roretzi or aurantium, and cultured under conditions of cleavage arrest always differentiated into an epidermal phenotype, showing long-lasting Ca2+-dependent action potentials and/or tunic on the cell surface. a4-2 blastomeres contacted by a chordamesodermal blastomere, A4-1, differentiated into a neural phenotype, characterized by fast Na+-dependent spikes. Differentiation to a similar neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Previous work in our laboratory (Okado & Takahashi, 1990b) has shown that neural differentiation was induced by cell contact with the blastomere, A4-1, which contains the presumptive notochordal area, only if contact occurred before the late gastrula stage; the same critical period existed when neural differentiation was induced by protease (Okado & Takahashi, 1990b, 1993.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work in our laboratory (Okado & Takahashi, 1990b) has shown that neural differentiation was induced by cell contact with the blastomere, A4-1, which contains the presumptive notochordal area, only if contact occurred before the late gastrula stage; the same critical period existed when neural differentiation was induced by protease (Okado & Takahashi, 1990b, 1993.…”
Section: Discussionmentioning
confidence: 99%
“…5A) and as large as that in protease-induced neurally differentiating cells. If a4-2 blastomeres are contacted with A4-1 blastomeres or treated with proteases after the late gastrula stage, neural induction does not occur and a4-2 blastomeres differentiate into epidermal-type cells (Okado & Takahashi, 1990b;1993). When the blastomere was treated with subtilisin at 15 h. later than the sensitive period for neural induction, the cell differentiated into an epidermal-type cell and exhibited the same level of inward-rectifier K+ channel current as that of cells not treated with protease (U in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation, cleavage arrest, neural induction, and culture of a4.2 cells were performed as previously described (Okamura et al, 1994). C ells were neurally induced either by treatment with 0.2% subtilisin for 1 hr or by cell-contact with A4.1 cell (Okado and Takahashi, 1993). Electrical recording was performed in the two-electrode voltage-clamp configuration using AxoC lamp2B (Axon Currents were elicited by membrane depolarization pulses ranging from Ϫ50 to ϩ80 mV in 10 mV increments after a 50 msec prepulse at Ϫ120 mV.…”
Section: Methodsmentioning
confidence: 99%
“…The disappearance of the Na ϩ current is very gradual and follows a complex time course, with a transient peak of density as the larval tail elongates (243). In a further elegant series of experiments, this group developed an in vitro two-cell neural induction system, in which individual cleavage-arrested neural-and notochord-lineage cells are placed into physical contact and subsequently separated to study the exact developmental timing of induction, as well as the timing of competence in each cell (454,455,457). With the use of this system, it was shown that neural induction triggered the expression of a neural-type Na ϩ channel whose biophysical properties were distinct from the Na ϩ channel expressed in the egg (461,462).…”
Section: B Early Postfertilization Changes and Selective Channel Elimentioning
confidence: 99%